Immediate Effects of Aerobic Exercise on Arterial Stiffness in a Male Population with Different Blood Glucose Levels - HE Rong, ZHANG Li, LI Peng, ZHANG Xiaoling, ZHANG Guo, ZANG Yiran, WU Shouling, SUN Lixia (Zhongguo quanke yixue, 2023)
Background Previous studies on the benefits of aerobic exercise mainly focus on the impact of aerobic exercise on long-term cardiovascular health and outcomes, namely regular aerobic exercise can improve arterial stiffness, while some studies point out that high blood sugar increases arterial stiffness. Objective To investigate the immediate effect of aerobic exercise on arterial stiffness in people with different blood glucose levels. Methods This study selected individuals who had participated in the 6th follow-up physical examination of the Kailuan Study during 2018—2020 and participated in the 5th national physical fitness surveillance in 2020 and completed their brachial-ankle pulse wave conduction velocity (baPWV) measured before and after the secondary load test of the power vehicle bicycle in four subordinate enterprises of Kailuan Group. Epidemiological survey result were collected: general information (age, hypertension, hyperlipidemia, history of antihypertensive drugs, etc.) , anthropometric indicators〔systolic blood pressure (SBP) , diastolic blood pressure (DBP) , etc.〕and biochemical indicators (fasting blood glucose, etc.) . baPWV measured in the secondary load test of the power vehicle bicycle (used as the aerobic exercise) was used as an indicator of upper and lower limb arterial stiffness. baPWV-related indicators〔SBP, DBP, mean arterial pressure (MAP) , heart rate (HR) , baPWV, metabolic equivalent (MET) , maximal oxygen uptake (VO2max) , etc.〕before and after the test were expressed using a unified form, for example, pre- and post-test baPWV were recorded as baPWV1 and baPWV2, respectively, and its pre- and post-test difference was denoted as ?baPWV. The epidemiological survey result and BAPWV-related data were compared between fasting blood glucose (FBG) quartile groups〔Q1 (n=220) : <5.00 mmol/L; Q2 (n=240) : 5.00-<5.40 mmol/L; Q3 (n=230) : 5.40-<5.81 mmol/L; Q4 (n=234) : ≥5.81 mmol/L〕. Generalized linear regression model was used to evaluate the association of FBG with pre- and post-test baPWV. Results A total of 924 eligible cases were enrolled, with an average age of (36.9±7.7) years. FBG quartile groups had statistically significant differences in mean age, hyperlipidemia and hypertension, history of using antihypertensive drugs, mean SBP, DBP, FBG, high sensitivity C-reactive protein, triglyceride, total cholesterol, high-density lipoprotein cholesterol and low-density lipoprotein cholesterol (P<0.01) . HR2 was found to be statistically significant higher than HR1 in groups Q1, Q2 and Q3 (P<0.01) . The baPWV2 was found to be statistically significant higher than baPWV1 in Q1, Q2, Q3 and Q4 groups (P<0.01) . SBP1, DBP1, MAP1 and baPWV1 significantly differed across the groups, and so did SBP2, DBP2, MAP2 and baPWV2 (P<0.01) . Compared with baPWV1, baPWV2 decreased by an average of 36.0 cm/s in people with different blood glucose levels. The generalized linear regression model showed that after adjusting for confounding factors, the ?baPWV level in group Q1 was lower than that in group Q4〔B (95%CI) =-18.96 (-36.96, -0.96) , P=0.04) 〕. Conclusion Aerobic exercise can immediately improve the degree of arterial stiffness, but the effect can be weakened by high blood sugar. Clinicians should design aerobic exercise programs according to the personal features of populations to improve arteriosclerosis and delay vascular aging.